Enhancing the Light Output of Solid-State Emitters - Woodhead, Christopher (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
The significance of the development of solid-state lighting was underscored by the award of a Nobel Prize in 2014. It is important to build upon this work and to produce practical and versatile sources of quantum light, because these are essential components for the advancement of quantum photonic devices. These devices, in turn, promise new technologies that have the potential to revolutionize society. This book explores various ways of coupling quantum light into, and out of, solid-state emitters. The research presented here has led to important discoveries that will help overcome major challenges in this field.